Impact of dioxins and polychlorinated biphenyls on kidney parameters: The modulatory role of vitamin D - Dongdong Zhang; Xixi Qiao; Juan Peng; Jingjing Quan; Zhijun Huang; Bin Yi (Ecotoxicology and Environmental Safety)
Background: Exposure to environmental chemicals may be a modifiable risk factor for the progression of chronic kidney disease (CKD). This study aimed to assess the impact of dioxin and polychlorinated biphenyl (PCB) exposures on urinary albumin-creatinine ratio (UACR) and estimated glomerular filtration rate (eGFR). Additionally, it explored the modulatory effect of vitamin D on this association. Methods: This cross-sectional study was based on the 1999–2012 National Health and Nutrition Examination Survey (NHANES). Multiple linear regression, weighted quantile sum (WQS) regression, and Bayesian kernel machine regression (BKMR) models were used to explore the associations of blood dioxins and PCBs with UACR and eGFR. Additionally, we analyzed the interaction effect of chemicals and vitamin D on UACR and eGFR. Results: In linear regression, six chemicals (PCB138, PCB153, PCB180, hexa-CDDs, hepta-CDDs and OCDD) showed positive correlations with UACR, and all seven chemicals (PCB138, PCB153, PCB180, hexa-CDDs, hepta-CDDs, OCDD, and HXCDF) were negatively correlated with eGFR. The WQS regression analysis revealed that the WQS index was correlated with both UACR (β = 0.21, 95 % CI: 0.14, 0.28) and eGFR (β = -6.15, 95 % CI:-7.30, −5.01).The BKMR analysis demonstrated that the overall exposure of the dioxins and PCBs was significantly associated with UACR and eGFR when all the chemicals were at or above the 55th percentile, compared to the 50th percentile. Interactions between serum vitamin D and chemicals on UACR were observed (P interaction < 0.05). Conclusion: Our findings suggest that overall dioxin and PCB exposure was significantly associated with UACR and eGFR. The higher vitamin D level might reduce UACR level related to dioxin and PCB exposure.